Realization to Extend the Orientation Estimation Range of Moving Target on the Ground by a Single Vector Sensor - Xiaopeng Song; Cong Zhang; Hong Liu; Guojun Zhang; Chenyang Xue (Institute of Advanced Engineering and Science, 2013)
The DOA (direction of arrival) estimation of seismic signals from the moving target on the ground bears great significance for unattended ground systems. The traditional DOA estimation of seismic signals is achieved by a sensor array and its corresponding algorithms. MEMS (Micro-Electro- Mechanical Systems) vector vibration sensor, however, gets the vector information over the propagation of seismic signals and therefore can get a DOA estimation within a certain range through a single vector sensor. This paper proposes a new method to extend the orientation range through the rotation of the MEMS vector vibration axis. The experiment shows that this method shares the merits with simple systematic structure, high sensitivity and less than 5 degrees of error on average, which has an extensive wide application prospect. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3893